Rosyjskie. Europejskie. Oświecone. Rozumne. O obecności Rosji w Azji Środkowej (i nie tylko) - Andrzej Polak (Studia Rossica Posnaniensia)
The author of the paper, using tools developed by postcolonial researchers, discusses the works of twentieth-century Russian writers. The setting of these texts is in the territory of Central Asia, Siberia or the Caucasus, constituting one of the factors defining them as the so-called Eastern text of Russian literature. Although most of the writers come from the other parts of Russia and – in most cases – are of Slavic descent, they know these regions quite well. These writers, however, are little interested in the problems of indigenous peoples, as long as they are not related to nationwide issues such as industrialization, collectivization or the labour camp system. The issues of destruction and loss of cultural identity, subordination, enslavement and exploitation of the local population are often omitted. The main characters in the works of Russian writers are invariably Russians, and their reference point is the Russian (Soviet) state.